2016
DOI: 10.1111/joss.12198
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Comparison of Consumer Acceptability of Kimchi with Different Degree of Fermentation

Abstract: Strong flavor developed during fermentation can affect foreign consumer's liking of kimchi (fermented vegetables with seasonings). This study was conducted to compare the cross-cultural preference of American versus Korean consumers for kimchi fermented to different degrees. Kimchi samples fermented to different degrees (pH 5.9, LFK; pH 4.2, MFK; and pH 3.9, HFK) were presented to American (n 5 111) and Korean consumers (n 5 101). The degree of liking and attribute intensities were assessed using the 9-point h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…A balance in gender (50:50, men–women) and the level of exposure to Kimchi (50:50, frequent–infrequent consumers) were also considered. A consumption frequency of once a month was selected as a criterion to distinguish infrequent and frequent consumers based on a previous study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A balance in gender (50:50, men–women) and the level of exposure to Kimchi (50:50, frequent–infrequent consumers) were also considered. A consumption frequency of once a month was selected as a criterion to distinguish infrequent and frequent consumers based on a previous study …”
Section: Methodsmentioning
confidence: 99%
“…Adaptation and a hedonic shift induced by long‐term exposure have been suggested as the mechanisms underlying acquisition of liking and increased tolerance of spiciness . A previous study, which focused on fermentation flavor and sourness of Kimchi, reported that consumption frequency of Kimchi is positively associated with the American consumers' preference for more fermented Kimchi. Considering Kimchi consumption is continuously increasing worldwide, it is reasonable to assume that a more authentic version of Kimchi may be accepted more favorably by frequent users.…”
Section: Introductionmentioning
confidence: 99%
“…Generating a method of sensory profiling and measuring consumer acceptability are the starting points needed to develop products to satisfy the quality standards that many consumers demand (Varela & Ares, ). Several studies have reported the descriptive profiles and/or consumer acceptability of Korean foods (Chambers, Lee, Chun, & Miller, ; Chang, Kwak, Yoo, & Lee, ; Jang, Kim, Lim, & Hong, ; Kim & Lee, ; Kwak, Ahn, Kim, & Lee, ). For doenjang , Kim, Hong, Song, Shin, and Kim () described the sensory characteristics and consumer acceptability of doenjang and reported that consumer acceptability was positively affected by sweetness and umami and negatively influenced by saltiness, meju , soy sauce, and fermented fish sauce flavors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is worth noting that although the general trend for overall liking and familiarity did not significantly differ between the 2 age groups (Table ), the overall liking and familiarity scores for the traditional‐type samples (TSB1 and TSB2) tended to be lower for YC than OC consumers. Product familiarity is one of the most important determinants influencing the overall liking of consumers for a traditional fermented food such as Doenjang (Choi et al., ; Chung et al., ; Hong et al., ; Jang et al., ; Yusop, O'Sullivan, Kerry, & Kerry, ). Because the present OC consumers were more likely to be exposed to such products, these consumers seemed to accept traditional‐type products better than did the YC consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when the samples were evaluated in soup, which is a form that is more familiar to consumers, the expectations may have played more important role, thus resulted in discrepancy in familiarity and preference for traditional‐type samples between YC and OC. Considering the importance of familiarity in association to expectation (Piqueras‐Fiszman & Spence, ) and overall acceptability of a product (Choi et al., ; Chung et al., ; Hong et al., ; Jang et al., ; Laing et al., ; Pagès, Bertrand, Ali, Husson, & Lê, ; Prescott, ; Prescott et al., , ; Yusop et al., ), assessing consumer responses for the representative consumed form can be critical for understanding the drivers of liking for condiments such as Doenjang .…”
Section: Resultsmentioning
confidence: 99%